1976
DOI: 10.1111/j.1476-5381.1976.tb07710.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Antagonists in Rat Hippocampus

Abstract: I Hippocampal cellular responses to acidic amino acids and some of their antagonists were measured in the rat anaesthetized with urethane. The effects of these antagonists on the field responses of the rat hippocampus to afferent stimulation were measured in acute as well as chronically prepared rats.2 Hippocampal pyramidal cells were excited by microiontophoretic application of glutamate and aspartate. These responses were antagonized by glutamic acid diethyl ester (GDEE), glutamic acid dimethyl ester (GDME) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

1978
1978
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(17 citation statements)
references
References 13 publications
1
13
0
3
Order By: Relevance
“…Moreover, they suggest that GLU rather than ASP acts as transmitter in this projection. This is in agreement with histochemical, electrophysiologic, and pharmacologic evidence indicating that GLU is the transmitter in the commissural and associational fibers of the CA3 pyramidal cells in the hippocampus (27)(28)(29). Because multiple fluorescent labeling showed that the majority of the hippocampal fibers projecting to the LSC originate in the very same population of CA3 cells (3 1 ), the same transmitter may be expected to be active in these projections.…”
supporting
confidence: 85%
“…Moreover, they suggest that GLU rather than ASP acts as transmitter in this projection. This is in agreement with histochemical, electrophysiologic, and pharmacologic evidence indicating that GLU is the transmitter in the commissural and associational fibers of the CA3 pyramidal cells in the hippocampus (27)(28)(29). Because multiple fluorescent labeling showed that the majority of the hippocampal fibers projecting to the LSC originate in the very same population of CA3 cells (3 1 ), the same transmitter may be expected to be active in these projections.…”
supporting
confidence: 85%
“…In the hippocampus, where the 5-HT terminals have a nonuniform distribution, the 5-HT receptors differed somewhat from those in platelets. Methysergide, cyproheptadine LSD and BOL 148 blocked the inhibitory responses to 5-HT whereas cinanserin, mianserin and methiothepin did not exhibit this effect (Segal, 1976;Haigler & Aghajanian, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…The shape change in platelet suspensions was determined with a Born Mark 3 aggregometer by measuring the maximal light absorption at 37°C (M in Figure 1) Segal, 1976). The samples were stirred with a Teflon-covered magnetic stirrer at about 900 revolutions per min.…”
Section: Measurement Of Shape Changementioning
confidence: 99%
“…study of GDEE in the frog spinal cord showed no antagonist activity at the three postsynaptic EAA receptors at concentrations up to 5 mm, and some apparently non-specific effects, with the inhibition of synaptic activity (Evans et al, 1979). In the hippocampus, though, a more selective action of GDEE against EAAs over ACh has been observed (Segal, 1976;Spencer et al, 1983).…”
Section: Introductionmentioning
confidence: 98%